SenseWeb: An Infrastructure for Shared Sensing - Kansal, Aman; Nath, Suman; Liu, Jie; Zhao, Feng (IEEE MultiMedia, 2007)
Peer-produced systems can achieve what might be infeasible for stand-alone systems developed by a single entity. Take Wikipedia, for example. Each contributor to the site provides a small piece of information. Coordinated effectively, the sum of the compositions yields something of far greater value than all the compositions individually.